1985
DOI: 10.1002/j.1551-8833.1985.tb05557.x
|View full text |Cite
|
Sign up to set email alerts
|

Metal Mobilization in Home Well Water Systems in Nova Scotia

Abstract: A study of private wells in rural Nova Scotia found that concentrations of metals such as cadmium, zinc, copper, and lead increased in water that remained in the distribution system overnight. Some 50 percent of the homes studied exceeded Canada's recommended 1.0‐mg/L maximum permissible limit for copper and 20 percent exceeded the 0.05‐mg/L limit for lead. Metal mobilization was observed in all four of the communities studied, regardless of differences in well water chemistry. Significant leaching was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Maessen et al [51] reported that the degree of leaching of some of the TEs was strongly related to some of the variable WQPs, such as conductivity, TDS, Cl − , 2 4 SO  , and 3 NO  . In this study, no correlations were observed among increases in Al, Co, Cr, Pb, and Ni and conductivity, Cl − , or 2 4 SO  .…”
Section: Resultsmentioning
confidence: 99%
“…Maessen et al [51] reported that the degree of leaching of some of the TEs was strongly related to some of the variable WQPs, such as conductivity, TDS, Cl − , 2 4 SO  , and 3 NO  . In this study, no correlations were observed among increases in Al, Co, Cr, Pb, and Ni and conductivity, Cl − , or 2 4 SO  .…”
Section: Resultsmentioning
confidence: 99%
“…Seventy-five percent of the zinc values were below 0.236 mg/L. Other investigators have attributed the higher concentrations of zinc in household tap waters, compared to finished drinking water, to distribution and transmission lines (Maessen et al 1985;Ohanian 1986;Schock and Neff 1988).…”
Section: Potential For Human Exposurementioning
confidence: 98%
“…Zinc has been detected in air (Barrie and Hoff 1985;Duce et al 1975;EPA 1980d;Evans et al 1984;John et al 1973;Lioy et al 1978;Lloyd and Showak 1984;Patterson et al 1977;Pratt et al 2000;Ragaini et al 1977;Saltzman et al 1985;Spicer et al 1996;Zoller et al 1974), water (Bruce and McMahon 1996;Coale and Flegal 1989;Cole et al 1984;EPA 1980d;Hale 1977;HazDat 2005;Heit et al 1989;Maessen et al 1985;Minear et al 1981;NAS 1977;Nriagu et al 1996;Ohanian 1986;Sañudo-Wilhelmy and Gill 1999;Schock and Neff 1988;Scudlark et al 1994;Shiller and Boyle 1985;Taylor et al 2001;Windom et al 1991), soil (Beavington 1975;Chen et al 1999;Connor and Shacklette 1975;EPA 1980d;Haines 1984;HazDat 2005;Mayer and Manning 1990;Mielke et al 1999Mielke et al , 2000Mumma et al 1984Mumma et al , 1990…”
Section: Potential For Human Exposurementioning
confidence: 99%
“…According to Maessen et al [65], parameters which are of importance in determining the extent of copper and lead leaching from pipes include potassium, sodium, calcium, magnesium, manganese chloride, nitrate, and sulfate. They analyzed home (drilled or dug) well water samples from a number of locations in Nova Scotia, Canada, for copper, zinc, lead and cadmium.…”
Section: Factors Influencing Drinking Water Qualitymentioning
confidence: 99%